THE IMPORTANT ROLE OF SHARIA ACCOUNTING IN INFORMATION SYSTEMS - Zulfikar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Accounting as an information system identifies collecting and communicating economic information about a business entity to various people. Accounting is at the forefront and plays an important role in running our economy and social system. Decisions taken by individuals, governments, other business entities are determined in terms of their use of the resources owned by a nation. One of the most important aspects of an entity is the financial aspect and financial reporting records that have a major impact on the sustainability of the entity. This research is an entirely research library. The purpose of this study is to determine how Islamic accounting is an information system. The analytical method used is the content analysis method. The results of this study indicate that Islamic accounting is an effort to deconstruct modern accounting in a humanist and value-laden form. Islamic accounting information systems highlight Islamic values ​​both in the object of accounting and information systems, Islamic accounting information systems have a great responsibility in moral matters.